Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Our platform connects you with professionals ready to provide precise answers to all your questions in various areas of expertise. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

Find the sum of the roots of the equation [tex]2x^2 + 3x - 9 = 0[/tex].

A. [tex]\(-18\)[/tex]
B. [tex]\(-6\)[/tex]
C. [tex]\(\frac{-9}{2}\)[/tex]
D. [tex]\(\frac{-3}{2}\)[/tex]


Sagot :

To find the sum of the roots of the quadratic equation [tex]\(2x^2 + 3x - 9 = 0\)[/tex], we use a property from algebra known as Vieta's formulas. Vieta's formulas relate the coefficients of a polynomial to sums and products of its roots.

For a quadratic equation of the form [tex]\(ax^2 + bx + c = 0\)[/tex], the sum of the roots [tex]\(r_1\)[/tex] and [tex]\(r_2\)[/tex] is given by:

[tex]\[ r_1 + r_2 = -\frac{b}{a} \][/tex]

Now, for the quadratic equation [tex]\(2x^2 + 3x - 9 = 0\)[/tex]:

- [tex]\(a = 2\)[/tex]
- [tex]\(b = 3\)[/tex]
- [tex]\(c = -9\)[/tex]

Using the formula to find the sum of the roots:

[tex]\[ r_1 + r_2 = -\frac{b}{a} = -\frac{3}{2} \][/tex]

Hence, the sum of the roots of the equation [tex]\(2x^2 + 3x - 9 = 0\)[/tex] is:

[tex]\[ -\frac{3}{2} \][/tex]

Therefore, the correct answer is [tex]\( \boxed{-\frac{3}{2}} \)[/tex].